Desmoplastic Fibroblastoma of the Maxillary Sinus - Hitashi, Dubey; Liu, Yong-Qian; Xinxiang, Zhao (Archives of Clinical and Medical Case Reports, 2021)
Desmoplastic fibroblastoma, also called collagenous fibroma, is an uncommon, firm, slow-growing, painless, benign fibrous soft tissue tumor [1] once in a while, including bone. Evans first described this tumor in 1995. The maxillary sinus is a very uncommon site for desmoplastic fibroblastoma. Men are two and a half times more likely than women to experience these neoplasms in their fifth or sixth decades of life. Subcutaneous tissue or near the deep aspect of the skin Muscles of the skeleton of the arm, for example, are common position shoulder, upper back, and posterior neck [3]. Desmoplastic fibroblastoma in the Maxillary sinus is a very rare location to have in the third decade of life by location and age. Here we intend to present a case report of this particular case.